Anthropometric study among adults of different ethnicity in Malaysia - Karmegam, Karuppiah; Salit, Mohd Sapuan; Ismail, Md Yusof; Ismail, Napsiah; Mohd Tamrin, Shamsul Bahri; Shuib, S.; Krishnan, G. Mohana; Palanimuthu, Seetha; Tamilmoli, P.; Mohd Jusoh, Mohd Hanapi (Academic Journals, 2011)
A study was done to determine the differences of anthropometrics data among three ethnic populations in Malaysia. Measurements were collected among 300 respondents representing 150 males and 150 females ranging from the age of 18 to 24 years. A total of thirty-three body dimensions were measured. The statistical test includes, mean, standard deviation, standard error of mean, coefficient of variation, minimum, maximum, 5th percentile, 50th percentile and 95th percentile for the various body dimension were tabulated. ANOVA F using post-hoc Scheffe test were performed to determine the significant differences between the means of anthropometric dimension and within the three ethnic’s. The result shows that the significant differences (p<0.05) in most of the measurements taken between the three ethnics and among the different genders respectively. The post-hoc Scheffe test indicated that the Malay male’s have the largest body size compared to the Chinese and Indian. In addition, the Chinese female’s have the largest body size compared to the Malay and Indian population. In the male and female population, Indian and Malay have the smallest body size respectively. As a conclusion, the results suggest that there are various body dimension differences between the ethnics in Malaysian population and there is a need to consider ethnicity aspect when designing for the Malaysian population.